Call for the 1968 Democratic National Convention (1968)
The document is the official Call for the 1968 Democratic National Convention, issued January 8, 1968, announcing that the Convention would convene in Chicago on August 26, 1968, to nominate candidates for President and Vice President and adopt a party platform. It sets forth rules affirming nondiscriminatory participation in party affairs, defining delegates as bona fide Democrats, and requiring Democratic National Committee members to support the Convention's nominees. The document details the distribution of convention votes, delegates, and alternates among the states and territories, totaling 2,622 convention votes and 5,611 total delegates including National Committee members. It explains the formula for apportionment, including electoral vote allocations, popular vote bonuses, victory bonuses, and automatic votes for National Committee members, as well as provisions for territories. Finally, it outlines procedures for selecting convention committee members and establishes rules governing press and media seating arrangements.